Revisiting deliberative policy analysis through systemic co-inquiry: some experiences from the implementation of the Water Framework Directive in England. (3rd September 2019) - Foster, Natalie; Ison, Ray; Blackmore, Chris; Collins, Kevin
ABSTRACT: Water governance is central to the crisis of the Anthropocene as climate change, population growth and changing demands for water are predicted to exacerbate threats to food, water and energy security and river functioning. Since 2000 the major policy setting in Europe for the governance of water has been the European Water Framework Directive (WFD). Empirically grounded post-positivist water governance research strongly anchored in interpretivist and constructivist systems' traditions akin to deliberative policy analysis (DPA) is reported. The case is made, based on the UK (England), that an opportunity to transform water governance has been lost because WFD implementation has been prescriptive, top-down and fails to engage with dynamic complexity. Some changes have emerged from the adoption of a Catchment-Based Approach (CaBA), partly triggered by threat to government of a judicial review, but governance praxis and trajectory remain contested. The paper reports on new pathways and options for change emerging from a systemic co-inquiry, a deliberative instrument, which emphasises the importance of institutionalising community action at catchment scale and re-framing the enactment of the Directive as part of an iterative social learning system for water governance. In the light of our findings, implications for future DPA scholarship are explored.